Strategi Meningkatkan Sikap Moderasi Beragama Di Kalangan Gen Z Dengan Pendekatan Filsafat Emmanuel Levinas Pada Prespektif Bahasa di Media Sosial - Abdul Ghoni Asror; Tommi Yuniawan; Imam Baehaqie (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2026)
Generation Z constitutes the largest age group in Indonesia, growing up as digital natives with unlimited access to social media, making them vulnerable to exposure to religious extremism and intolerance. This study aims to formulate strategies to enhance religious moderation among Gen Z through the lens of Emmanuel Levinas' philosophy, particularly from the perspective of language use on social media. Employing a descriptive qualitative method through in-depth interviews, observations, and literature review in Bojonegoro, Tuban, and Lamongan regencies, the study found that 73% of participants struggled to distinguish between constructive criticism and hate speech, while 34% had been exposed to intolerant content. The application of Levinas' concept of "the face of the Other" proved effective in transforming participants' linguistic behavior toward more inclusive and responsible communication. This study recommends integrating Levinasian ethics into religious education curricula and digital literacy programs to support the eighth agenda of the Asta Cita program on strengthening interreligious tolerance.Keywords:  Religious moderation, Generation Z, Emmanuel Levinas, social media language